Authoritarian Predispositions and Attitudes towards Redistribution - Arikan, Gizem (My University, 2019)
﻿Authoritarian predispositions are associated with a preference for order, certainty and security. Using data from European Social Surveys (ESS), we show that this association extends to attitudes towards redistributive policies. We demonstrate that support for redistributive policies that emphasize the government’s responsibility to provide old age, health and unemployment benefits are positively associated with authoritarian predispositions. We also provide evidence that perceived economic threats moderate this relationship such that, for individuals who perceive higher levels of economic threat, the relationship between authoritarian predispositions and support for government responsibility is stronger. These results show that authoritarian predispositions are not only associated with social preferences but also attitudes towards economic policies.
PUBLISHED
Keywords: Authoritarianism; Redistribution; Ideology; Threat; Values; Inclusive Society